Sejarah dan Perkembangan serta Permasalahan Pendidikan Inklusi di Indonesia - Nurfadhillah, Septy; Ramadani, Faizaria Cahya Tri; Hidayati, Nurlayla; Nurwahyuni, Eka; Nur’alfiah, Siti; Ananda, Putri Syifa; Nazifah, Ismiatun; Hukmah, Fakah (ARZUSIN, 2022)
This study aims to reveal the history and development and problems of inclusive education. Inclusive schools provide educational programs that are appropriate, challenging, but according to the abilities and needs of each student as well as the help and support that teachers can provide for children to succeed. The history of the development of inclusive education in the world was originally initiated and started from Scandinavian countries (Denmark, Norway, Sweden). In the United States in the 1960s, President Kennedy sent Special Education experts to Scandinavia to study the mainstreaming and Least restrictive environment which turned out to be suitable to be applied in the United States. The research method used in this research is descriptive qualitative. The data collection technique used is triangulation. This research uses source triangulation and technique triangulation. After that, the data was analyzed through four stages, namel y: data collection, data reduction, data presentation and drawing conclusions. The results of the data obtained from observations and interviews. By interviewing third grade teachers at SDIT Latansa Cendekia, it was conducted using an interview guide to obtain information about inclusive education at SDIT Latansa Cendekia.